A native plant growth promoting bacterium, Bacillus sp. B55, rescues growth performance of an ethylene-insensitive plant genotype in nature - Meldau, Dorothea G.; Long, Hoang H.; Baldwin, Ian T. (Frontiers in Plant Science, 2012)
Many plants have intimate relationships with soil microbes that through a variety of mechanisms improve the plant’s growth and fitness. Bacillus megaterium is a natural endophyte isolated from Nicotiana attenuata plant roots growing in native soils. A particular isolate (B55), was found to have dramatic plant growth promoting (PGP) effects on wild type (WT) and transgenic plants impaired in ethylene (ET) perception (35S-etr1), the genotype from which this bacteria was first isolated. B55 not only improves N. attenuata growth under in vitro, glasshouse and field conditions, but it also “rescues” many of the deleterious phenotypes associated with ET insensitivity. Most notably, B55 dramatically increases the growth and survival of 35S-etr1 plants under field conditions. To our knowledge, this is the first demonstration of a PGP effect in a native plant-microbe association under natural conditions. Our study demonstrates that this facultative mutualistic plant-microbe interaction should be viewed as part of the plant’s extended phenotype. Possible modalities of recruitment and mechanisms of PGP are discussed.